2015
DOI: 10.1107/s1600576714027770
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelasticity of SrCo0.8Fe0.2O3–δperovskite-related oxide with mixed ion–electron conductivity

Abstract: A group-theoretical analysis was carried out to determine the possible orientation states of domains formed as a result of the 'perovskitebrownmillerite' phase transition in SrCo 0.8 Fe 0.2 O 2.5 oxide with mixed ionelectron conductivity (MIEC). The results of the theoretical analysis agree with the experimental data obtained in the study of the SrCo 0.8 Fe 0.2 O 2.5 microstructure by means of transmission electron microscopy. Brownmillerite SrCo 0.8 Fe 0.2 O 2.5 (BM) has a lamellar texture composed of 90 twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…34,35 Previously we demonstrated that the P-BM phase transition in MIEC oxide SrCo 0.8 Fe 0.2 O 2.5 is ferroelastic: a change of point symmetry is accompanied by the formation of 90 twins, which may be reoriented by external mechanical stress. 36,37 An increase in the compositional disorder due to the oxygen nonstoichiometry in SrCo 0.8 Fe 0.2 O 2.5AEx is accompanied by the phenomena similar to those observed in relaxor ferroelectrics (in terms of its microstructural features), namely the formation of nanosized brownmillerite domains in the low-temperature (ferroelastic) phase.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…34,35 Previously we demonstrated that the P-BM phase transition in MIEC oxide SrCo 0.8 Fe 0.2 O 2.5 is ferroelastic: a change of point symmetry is accompanied by the formation of 90 twins, which may be reoriented by external mechanical stress. 36,37 An increase in the compositional disorder due to the oxygen nonstoichiometry in SrCo 0.8 Fe 0.2 O 2.5AEx is accompanied by the phenomena similar to those observed in relaxor ferroelectrics (in terms of its microstructural features), namely the formation of nanosized brownmillerite domains in the low-temperature (ferroelastic) phase.…”
Section: Introductionmentioning
confidence: 73%
“…To emphasize the microstructural similarity with relaxor ferroelectrics, we proposed to use a term "relaxor ferroelastic" for MIEC ferroelastics with high degree of compositional disorder, in which the phase transition is smeared and the low-temperature (ferroelastic) phase has nanosized texture. 36 It is evident that the resemblance in the progress of phase transitions and microstructural features of low-temperature phases for ferroelectrics and ferroelastics (see Fig. 10-12) is related to the common nature of ferroelectricity and ferroelasticity based on the crystal lattice distortion.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations